Pragmatic Strategy : Eastern Wisdom, Global Success / [electronic resource] - Nonaka, Ikujiro; Zhu, Zhichang (Cambridge : Cambridge University Press, 2012)
Pragmatism is enjoying a renaissance in management studies and the social sciences. Once written off as amoral, relativist and opposed to the ideals of Truth, Reason and Progress, it is now regaining influence in public policy, international relations and business strategy. But what can pragmatism teach us about strategy? How can pragmatic strategies help businesses to succeed? This innovative book presents a pragmatic framework for shaping and solving strategic problems in a practical, creative, ethical and finely balanced manner. To achieve this, the authors draw from Confucian teaching, American pragmatism and Aristotelian practical wisdom, as well as business cases across industries and nations, particularly from emerging economies. With significant theoretical depth, direct practical implication and profound cultural sensitivity, the book is useful for executive managers, public administrators, strategy researchers and advanced students in the search for pragmatic strategies in an interconnected, fast-moving world.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Strategic planning; Pragmatism; Confucianism; Management; Comparative management